Strategi Komunikasi Band Indie Elephant Kind dalam Perkembangan Subsektor Musik Indonesia - Kevin Septanto K. Prakoso; Dhita Widya Putri (Universitas Multimedia Nusantara, 2018)
Music is part of mass communication products developing in the recording industry. Music industry is evolving along with technology and communication advancement. In Indonesia, music is part of the Creative Economy Agency's subsector and considered as one of the promising industries, as there are creative activities such as creation, production, distribution, and promotion. This phenomenon fosters the emergence of indie music industry which perform all activities independently, such as Elephant Kind music band. This study examines how Elephant Kind contributes to indie music sector in Indonesia with their communication strategy approach. By qualitative methods, in-depth interviews and observation, the result shows that Elephant Kind has developed their own strategies to achieve goals based on Pace, Peterson, and Burnett central goals such as 'to secure understanding, to establish acceptance, and to motivate action'. Future research is expected to measure the impact of the communication strategies through the public perceptions. Keywords: communication strategy, music, indie band, mass communication